Research on High-Quality Development of Patriotism Education for Border Preschool Children Empowered by Digital Technology - Qin, Ning; Yuan, Minling (Journal of Educational Research and Policies, 2025)
In the context of high-quality development of basic education , patriotism education faces key questions such as for whom to cultivate talent, how to cultivate talent, and what kind of talent to cultivate. Digitalization of education relies on all parties working together around shared value propositions, utilizing digital technology to stimulate educational innovation, and designing a collaborative governance framework with multi-party participation and resource convergence. Adhering to the concept of starting from a young age, this paper points out that the “practice schema” encompasses elements such as habits, intentions, time, and context, providing a theoretical framework for understanding the integration of digital technology in educational development. Based on the practice of digital transformation in early childhood patriotism education, this paper optimizes the details of educational practice by solving practical problems, thereby promoting the healthy growth of children.